Long-Acting Injectable Cabotegravir + Rilpivirine for HIV Maintenance Therapy: Week 48 Pooled Analysis of Phase 3 ATLAS and FLAIR Trials. (1st December 2020) - Rizzardini, Giuliano; Overton, Edgar T.; Orkin, Chloe; Swindells, Susan; Arasteh, Keikawus; Górgolas Hernández-Mora, Miguel; Pokrovsky, Vadim; Girard, Pierre-Marie; Oka, Shinichi; Andrade-Villanueva, Jaime F.; Richmond, Gary J.; Baumgarten, Axel; et al.
Abstract : Background: Long-acting (LA) injectable regimens are a potential therapeutic option in people living with HIV-1. Setting: ATLAS (NCT02951052) and FLAIR (NCT02938520) were 2 randomized, open-label, multicenter, multinational phase 3 studies. Methods: Adult participants with virologic suppression (plasma HIV-1 RNA <50 copies/mL) were randomized (1:1) to continue with their current antiretroviral regimen (CAR) or switch to the long-acting (LA) regimen of cabotegravir (CAB) and rilpivirine (RPV). In the LA arm, participants initially received oral CAB + RPV once-daily for 4 weeks to assess individual safety and tolerability, before starting monthly injectable therapy. The primary endpoint of this combined analysis was antiviral efficacy at week 48 (FDA Snapshot algorithm: noninferiority margin of 4% for HIV-1 RNA ≥50 copies/mL). Safety, tolerability, and confirmed virologic failure (2 consecutive plasma HIV-1 RNA ≥200 copies/mL) were secondary endpoints. Results: The pooled intention-to-treat exposed population included 591 participants in each arm [28% women (sex at birth), 19% aged ≥50 years]. Noninferiority criteria at week 48 were met for the primary (HIV-1 RNA ≥50 copies/mL) and key secondary (HIV-1 RNA <50 copies/mL) efficacy endpoints. Seven individuals in each arm (1.2%) developed confirmed virologic failure; 6/7 (LA) and 3/7 (CAR) had resistance-associated mutations. Most LA recipients (83%) experienced injection site reactions, which decreased in incidence over time. Injection site reactions led to the withdrawal of 6 (1%) participants. The serious adverse event rate was 4% in each arm. Conclusion: This combined analysis demonstrates monthly injections of CAB + RPV LA were noninferior to daily oral CAR for maintaining HIV-1 suppression.